The Present Position and Prospects of the British Trade with China Together with an Outline of Some Leading Occurrences in its Past History - Matheson, James 1796-1878 (Cambridge library collection. East and South-East Asian History, 1836)
James Matheson (1796–1878) became a leading taipan, with significant influence and power in Hong Kong. When this pamphlet was published, in 1836, he was still trading from Canton (Guangzhou) and, following the abolition of the East India Company's monopoly on trade with China, appealed to the British government to pressure the Chinese to lift the severe restrictions on trading. He suggests that despite the efforts of the merchants, China refuses to acknowledge the law of nations, to trade fairly, and as such has 'long since surrendered her rights and is no longer in a position to enforce them'. Matheson's personal appeal to the Duke of Wellington was rebuffed, but his business partner, William Jardine, later persuaded Lord Palmerston to adopt a tougher approach, which ultimately led to the First Opium War. This is a powerful and provocative text: a defence of both free trade and an aggressive foreign policy